Experimental study on the mechanical properties and failure modes of BFRP bar anchor systems under static tension loading - Dai, Zhenwei; Zhou, Shengtao; Yin, Yueping; Fu, Xiaolin; Zhang, Yanjun; Guo, Jinjun; Du, Zhigang; Tao, Yawen; Wu, Xiaolei (Frontiers in Earth Science, 2023)
Basalt fiber-reinforced polymer bars are lightweight composite materials with high strength, low density, and excellent corrosion resistance. The anchor system made from basalt fiber-reinforced polymer bars is worthy of being developed and expected to be used in rock anchoring projects. In this work, four different basalt fiber-reinforced polymer anchor systems were designed, the influences of different design parameters on the ultimate bearing capacity of the anchor system were investigated through tension tests, and the failure modes of different anchor systems were elucidated. The test results indicated that failure modes, such as the transverse fracture of these bars and debonding of the bonding medium, were widely present in the wedge-modified anchor system and the steel-pipe-protected anchor system. These two anchor systems performed poorly with the wedge anchorage, whereas the basalt fiber-reinforced polymer bars protected by seamless steel pipes burst under the tension imposed by a universal testing machine. The threaded steel-pipe-bonded anchor system and the steel strand–basalt fiber-reinforced polymer bar composite anchor system had maximum anchorage efficiency coefficients of 97.7% and 98.5%, respectively. The bars in the corresponding test groups all exhibited burst failure, indicating that these two anchoring structures achieved effective anchorage of the basalt fiber-reinforced polymer bars.